An empirical investigation into the word of mouth communication in building consumer based brand equity of personal care products - Vasan, M.; Rangasamy, K.S. (University of Jaffna, 2016)
WOM communication is one of the most powerful forces in the marketplace and tends to be highly persuasive and, in turn, extremely effective. It is accepted that this form of communication has valuable source credibility. It occurs on a regular basis amongst friends and families and has been recognized as an important promotional tool for organizations. There is a close and inseparable relationship between WOM communication and brand equity for a product or service. The reason is that, through WOM communication, customers can contribute to the image of product or service. This ultimately reflects on building image or equity for a product or service. Keeping this reality in mind, this study investigates the role of WOM communication on Consumer Based Brand Equity (CBBE) of personal care products. This study is conducted through a survey method among 720 users of personal care products. The study, by using factor analysis, identified seven predominant factors influencing WOM communication, such as, information sharing desire, reciprocity, self enhancement, source credibility, brand selection, purchase decision and opinion seeking. The result of the analysis reveals that there is a high degree of positive correlation between the WOM communication and brand equity (0.60). It indicates that positive information through WOM communication effectively influences the Consumer-based Brand Equity of personal care products. As a result, the sellers understand the effectiveness of WOM communication and takes utmost care to see that positive WOM is spread and customer base is increased.
Keywords: Brand equity; Factor analysis; Personal care Products; Structural equation modeling; Word of mouth